Recommended approaches to the scientific evaluation of ecotoxicological hazards and risks of endocrine‐active substances. (27th January 2017) - Matthiessen, Peter; Ankley, Gerald T; Biever, Ronald C; Bjerregaard, Poul; Borgert, Christopher; Brugger, Kristin; Blankinship, Amy; Chambers, Janice; Coady, Katherine K; Constantine, Lisa; Dang, Zhichao; Denslow, Nancy D; et al.
ABSTRACT: A SETAC Pellston Workshop ® "Environmental Hazard and Risk Assessment Approaches for Endocrine‐Active Substances (EHRA)" was held in February 2016 in Pensacola, Florida, USA. The primary objective of the workshop was to provide advice, based on current scientific understanding, to regulators and policy makers; the aim being to make considered, informed decisions on whether to select an ecotoxicological hazard‐ or a risk‐based approach for regulating a given endocrine‐disrupting substance (EDS) under review. The workshop additionally considered recent developments in the identification of EDS. Case studies were undertaken on 6 endocrine‐active substances (EAS—not necessarily proven EDS, but substances known to interact directly with the endocrine system) that are representative of a range of perturbations of the endocrine system and considered to be data rich in relevant information at multiple biological levels of organization for 1 or more ecologically relevant taxa. The substances selected were 17α‐ethinylestradiol, perchlorate, propiconazole, 17β‐trenbolone, tributyltin, and vinclozolin. The 6 case studies were not comprehensive safety evaluations but provided foundations for clarifying key issues and procedures that should be considered when assessing the ecotoxicological hazards and risks of EAS and EDS. The workshop also highlighted areas of scientific uncertainty, and made specific recommendations for research and methods‐development to resolve some of the identified issues. The present paper provides broad guidance for scientists in regulatory authorities, industry, and academia on issues likely to arise during the ecotoxicological hazard and risk assessment of EAS and EDS. The primary conclusion of this paper, and of the SETAC Pellston Workshop on which it is based, is that if data on environmental exposure, effects on sensitive species and life‐stages, delayed effects, and effects at low concentrations are robust, initiating environmental risk assessment of EDS is scientifically sound and sufficiently reliable and protective of the environment. In the absence of such data, assessment on the basis of hazard is scientifically justified until such time as relevant new information is available. Integr Environ Assess Manag 2017;13:267–279. © 2017 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: This consensus paper, developed using a cross section of international expertise, provides scientific information on current best practices in the evaluation of hazards and risks to wildlife populations of endocrine‐active substances (EAS) and endocrine‐disrupting substances (EDS). This paper, and the workshop on which it is based, concludes that if EDS data on environmental exposure, effects on sensitive species and life stages, delayed effects, and effects at low concentrations are robust, then environmental risk assessment is scientifically sound and sufficiently reliable. Areas of scientific uncertainty are highlighted and specific recommendations made for research and methods development, based on crosscutting issues that may impact decision making, all emerging from the case studies performed in preparation for the workshop. If suitable test or modeling methods are unavailable, the only alternative may be to regulate the substance on the basis of hazard alone, at least until such time as relevant additional data become available.